The Quran and Medical Sciences: An Interdisciplinary Exploration of Divine Revelation and Contemporary Health Knowledge - Romesa Maryam; Mah Rukh (Journal of Religion and Society, 2025)
This paper examines the dynamic relationship between Quran and modern medical sciences with special focus on the Quran as a source of guidance not just as a spiritual guide, but also as a source of knowledge that sheds much light in cases of human health, hygiene, nutrition, psychology and physiological developments. Based on the assumption that all knowledge is created by Allah, the Quran includes the need to contemplate the natural world and it calls on believers to study scientifically and to participate in scientific research as a way of worship and intellectual exploration. Among the most significant fields to be explored are embryology, in which passages in the Quran detailing a human developing in the womb are very similar to the processes known in modern medicine; nutrition, in which nutrition guidelines are similar to those of modern health advice; and mental health, in which the Quran focuses on inner peace through prayer and remembrance which is matched by references in modern psychology and neuroscience. Moreover, insistence on personal and public hygiene in the Quran anticipates the modern epidemiology and disease prevention principles. The methodological issues which arise in trying to fit the scriptural interpretation and the empirical science are also critically evaluated in this interdisciplinary work. It warns of excessively concordist interpretations, and emphasizes the necessity of theological integrity in the quest of scientific parallels. The article relies on the classical Islamic scholarship and contemporary scientific texts to advance an integrative approach, which regards science and revelation as complementary and not mutually exclusive. Finally, it places the case of a responsible interaction with both the Quran and science one that does not encroach on the epistemological domains of either and yet is sensitive to the common aim that both are attempting to pursue, the overall well-being of mankind. Keywords: Quran, Science, Islam, Quranic Embryology, Islamic Nutrition, Mental Health, Islamic Hygiene, Divine Knowledge, Interdisciplinary Studies, Faith, Reason